Rates of Adverse IBD-Related Outcomes for Patients With IBD and Concomitant Prostate Cancer Treated With Radiation Therapy. Issue 5 (14th August 2019) - Feagins, Linda A; Kim, Jaehyun; Chandrakumaran, Anchalia; Gandle, Cassandra; Naik, Katrina H; Cipher, Daisha J; Hou, Jason K; Yao, Michael D; Gaidos, Jill K J
Abstract: Background: Patients with inflammatory bowel disease (IBD) may be at higher risk for complications from radiation treatment for prostate cancer. However, available data are limited, and controversy remains regarding the best treatment approach for IBD patients who develop prostate cancer. Methods: A retrospective cohort study across 4 Department of Veterans Affairs hospital systems. Patients with established IBD who were diagnosed and treated for prostate cancer between 1996–2015 were included. We assessed for flares of IBD, IBD-related hospitalizations, and IBD-related surgeries within 6, 12, and 24 months of cancer diagnosis and survival at 1, 2, and 5 years. Flares of IBD were those documented as such by the treating physician, and treatment changed accordingly. Results: One hundred patients with IBD and prostate cancer were identified. Forty-seven were treated with either treatment with external beam radiation or brachytherapy, and 53 were treated with nonradiation modalities. Comparing cohorts with or without radiation treatment, there were no differences in baseline IBD characteristics, Charlson comorbidity index, or prostate cancer stage. Inflammatory bowel disease flares were 2-fold higher for radiation-treated patients within 6 months (10.6% vs 5.7%) and 6–12 months (4.3% vs 1.9%) after cancer diagnosis. On multiple logistic regression analysis, radiation treatment (adjusted odds ratio, 4.82; 95% confidence interval, 1.15–20.26) was a significant predictor of flares. However, rates of IBD-related hospitalizations or surgeries were not significantly different. Conclusions: In this retrospective, multicenter study, 2-fold higher rates of flare were found within the first year after prostate cancer diagnosis for patients treated with radiation, but there were no differences in IBD-related hospitalizations or surgeries. Although patients should be counseled of these risks, avoidance of radiation therapy in IBD patients with prostate cancer is likely not necessary. Abstract : In this retrospective, multicenter study of inflammatory bowel disease (IBD) patients with prostate cancer, 2-fold higher flare rates were found within the first year after cancer diagnosis for radiation- vs non-radiation-treated patients but there were no differences in IBD-related hospitalizations or surgeries.